Trials and tribulations of conducting bio-behavioral surveys in prisons: implementation science and lessons from Ukraine. Issue 2 (13th June 2016) - Azbel, Lyuba; Grishaev, Yevgeny; Wickersham, Jeffrey A; Chernova, Olena; Dvoryak, Sergey; Polonsky, Maxim; Altice, Frederick L
Abstract : Purpose: – Ukraine is home to Europe's worst HIV epidemic, overwhelmingly fueled by people who inject drugs who face harsh prison sentences. In Ukraine, HIV and other infectious diseases are concentrated in prisons, yet the magnitude of this problem had not been quantified. The purpose of this paper is to evaluate the systematic health survey of prisoners in the former Soviet Union (FSU). Design/methodology/approach: – Qualitative interviews were carried out with research and prison administrative staff to assess the barriers and facilitators to conducting a bio-behavioral survey in Ukrainian prisons. Findings: – Crucial barriers at the institutional, staff, and participant level require addressing by: first, ensuring Prison Department involvement at every stage; second, tackling pre-conceived attitudes about drug addiction and treatment among staff; and third, guaranteeing confidentiality for participants. Originality/value: – The burden of many diseases is higher than expected and much higher than in the community. Notwithstanding the challenges, scientifically rigorous bio-behavioral surveys are attainable in criminal justice systems in the FSU with collaboration and careful consideration of this specific context.